Dynamic allocation policies for the finite horizon one armed bandit problem - Burnetas, AN; Katehakis, M.N. (Stochastic Analysis and Applications, 1998)
The unknown performance of a new experiment is to be evaluated and compared with that of an existing one over a finite horizon. The explicit structure of an optimal sequential allocation policy is obtained under pertinent reward/loss functions, when the experiments are characterized by random variables with distributions from the one parameter exponential family.